Policy Recommendations for Promoting Trust in Science through Integrity, Integration, and Communication - Ravn, Tine; Fuglsang, Simon (CFA Scientific Reports, 2025)
This report contains the POIESIS Final Policy Recommendations for Promoting Trust in Science through Integrity, Integration, and Communication. POIESIS provides a set of nine recommendations that highlight how European and national policymakers, research performing organisations, research funding organisations, researchers, and mediators can work to maintain trust in science and address current and future challenges. These recommendations address the three core areas of research integrity, societal integration in science, and science mediation, and build directly on the findings of the POIESIS project to provide robust empirically founded recommendations.